Ayat Accompaniment Of Allah The Holy Quran "Rhetorical Read" - Ahmed Mohammed , Shaymaa (Journal of College of Education, 2021)
The term “Ma’aiyet-Allah” , hence forth the companionship of Allah, has come in the Holy Qur’an with numerous denotations. In this research, we have touched upon two essential meanings representing the general companionship of Allah to the whole of his creation, and the private companionship of Allah related to his angels, prophets and righteous believers. The general companionship of Allah means that Allah is with all his creation, with his knowledge, awareness and inclusiveness. It has been mentioned in three places in the Holy Quran. While the private companionship of Allah has been mentioned in 17 places in the Holy Quran, and it means protection, support, informing and care. It is exclusively dedicated to Allah’s angels, prophets, and righteous believers.